Medición del tiempo de propagación de ondas para estimar rigidez de árboles en pie de Pino híbrido F1 INTA-PINDO - Winck, Rosa Ángela (2019)
The TreeSonic microsecond timer was designed for prediction of tree stiffness. It measures the stress wave time between a start and a stop transducer, from a known distance. Then the speed is calculated and with the density of the material, it allows estimating standing trees elasticity modulus. The objective of the work was to estimate the dynamic elasticity modulus through the wave propagation speed, at 10 and 11 years of 2 of hybrid pine progenies test.